2023
DOI: 10.21037/acs-2023-adw-0083
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiothoracic surgery in women with Turner syndrome

Lucas Ribé,
Ferial D. Shihadeh,
Rana O. Afifi
et al.

Abstract: Background To describe short- and mid-term surgical outcomes of patients with Turner syndrome (TS) after cardiovascular interventions. Methods All individuals >12 years of age at the time of surgical repair for cardiovascular disease (valve or coarctation repairs, aortic disease, aortic dissection) from 2002 to 2022 were eligible. The primary endpoint was complications or death within 30 days of intervention. Secondary outcomes included late complications and reinterven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Data from these follow up studies were stored in separate REDCap projects and exported to the TSRR after de-identification. Using this approach, TSRR investigators identified health disparities in access to guideline-recommended medical care for Spanish speakers with TS [ 13 ]; characterized the increased prevalence of dermatologic diseases in TS [ 14 ]; and described risk factors for postoperative complications after cardiovascular surgeries in young adults with TS, which occur more frequently than expected [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data from these follow up studies were stored in separate REDCap projects and exported to the TSRR after de-identification. Using this approach, TSRR investigators identified health disparities in access to guideline-recommended medical care for Spanish speakers with TS [ 13 ]; characterized the increased prevalence of dermatologic diseases in TS [ 14 ]; and described risk factors for postoperative complications after cardiovascular surgeries in young adults with TS, which occur more frequently than expected [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…BAV (15-30%), aortic coarctation (7-20%), and, less commonly, hypoplastic left heart syndrome [93,94] are common in patients with Turner syndrome (45, XO karyotype). Patients with Turner syndrome have an increased risk of left-sided obstruction lesions due to altered gene dosages on chromosome X and copy number polymorphisms at the 12q13.31 locus [95][96][97]. However, it is currently unknown how these genotypes affect the development of left-sided structures.…”
Section: Interference With Human Cardiac Development and The Occurren...mentioning
confidence: 99%
“…The TSRR has enrolled more than 1,100 participants and successfully deployed two general health update surveys and three project-speci c surveys (Supplementary Data). TSRR data has led to projects on skin concerns across the life spectrum and complications after cardiovascular surgeries [12]. Survey responses from these projects will be available to future researchers who apply for TSRR data.…”
Section: Research Progressmentioning
confidence: 99%